2021
DOI: 10.14740/jmc3632
|View full text |Cite
|
Sign up to set email alerts
|

Rare Surgical Complication of In Vitro Fertilisation Treatment: Bladder Injury During Oocyte Retrieval

Abstract: Current literature suggests that surgical complications from oocyte retrievals (ORs) are uncommon. Here, we present a rare case of bladder injury during OR and its subsequent management. A 37-year-old nulliparous woman underwent assisted reproductive therapy (ART) for primary infertility secondary to anovulatory cycle. During OR, there was an inadvertent puncture of the bladder, with active intra-bladder bleeding seen on transvaginal ultrasound. Bladder washout followed by continuous drainage was instituted wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…No duplication of the studies or use of the same population of patients was found. After screening the titles and abstracts of publications, hemoperitoneum cases due to adjacent vessel lesions (n = 3) were excluded [ 15 , 16 , 17 ], as well as those from urinary tract lesions (n = 6) [ 10 , 31 , 32 , 33 , 34 , 35 ]. Out of all full-text articles assessed for eligibility, 26 publications and 7 reports were excluded due to unknown bleeding sources causing hemoperitoneum or unclear presentation of patient data [ 5 , 6 , 26 , 36 , 37 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No duplication of the studies or use of the same population of patients was found. After screening the titles and abstracts of publications, hemoperitoneum cases due to adjacent vessel lesions (n = 3) were excluded [ 15 , 16 , 17 ], as well as those from urinary tract lesions (n = 6) [ 10 , 31 , 32 , 33 , 34 , 35 ]. Out of all full-text articles assessed for eligibility, 26 publications and 7 reports were excluded due to unknown bleeding sources causing hemoperitoneum or unclear presentation of patient data [ 5 , 6 , 26 , 36 , 37 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…We focused on hemoperitoneum as a result of ovarian bleeding with surgery performed for hemostasis, and not from bleeding from other sources, such as injury of blood vessels [ 15 , 16 , 17 , 39 ] or from bladder and ureteral injuries [ 10 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation